[Frederick Street, Port of Spain] - (:unkn) unknown (My University, 2010)
Frederick Street circa 1907-1920s showing one of the main shopping areas in Port of Spain. Stores were shaded by overhanging awnings with the name of the stores printed on them.
Colour: Black and white; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; Streets--Trinidad and Tobago; Pedestrians--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Hats--Trinidad and Tobago; Stores, Retail--Trinidad and Tobago; Street-railroads--Trinidad and Tobago; Architecture--Trinidad and Tobago; Signs and signboards--Trinidad and Tobago; Bicycles--Trinidad and Tobago; Wrought iron--Trinidad and Tobago; Clocks and watches--Trinidad and Tobago; Sidewalks--Trinidad and Tobago; Frederick Street (Port of Spain)